1972
DOI: 10.1136/gut.13.12.976
|View full text |Cite
|
Sign up to set email alerts
|

Plasmaphoresis and plasma exchange in the treatment of hyperlipaemia and xanthomatous neuropathy in patients with primary biliary cirrhosis

Abstract: SUMMARY Two patients with primary biliary cirrhosis who were increasingly incapacitated by xanthomatous neuropathy are described. Treatment with a low fat diet and cholestyramine was unhelpful but repeated plasmaphoresis by simple venesection in one and plasma exchange using an IBM blood cell separator in the other over a period of several months completely relieved the symptoms of the neuropathy, caused skin xanthomata to recede, and lowered plasma lipid levels in both patients. There was no evidence that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The burning pain experienced in the lesions may be the result of neural involvement, which can be a feature of other florid xanthomata, occurring in-for example, type V hyperlipoproteinaemia 24 and primary biliary cirrhosis. 25 As new cases of NXG arise, immunohistochemistry of fresh biopsy material for metalloproteinases may provide further insight into its pathogenesis and may also contribute to our understanding of atheromatous plaque rupture. (1) indicates the start of the glycine elution.…”
Section: Discussionmentioning
confidence: 99%
“…The burning pain experienced in the lesions may be the result of neural involvement, which can be a feature of other florid xanthomata, occurring in-for example, type V hyperlipoproteinaemia 24 and primary biliary cirrhosis. 25 As new cases of NXG arise, immunohistochemistry of fresh biopsy material for metalloproteinases may provide further insight into its pathogenesis and may also contribute to our understanding of atheromatous plaque rupture. (1) indicates the start of the glycine elution.…”
Section: Discussionmentioning
confidence: 99%
“…Primary biliary cirrhosis (PBC) is a condition that leads to accumulation of cholesterol. Turnberg et al showed successful clearance of cholesterol and relief of xanthomatous neuropathy by plasmapheresis [17]. There is no good evidence to confirm that accumulation of bile salts in PBC is reduced with plasma exchange.…”
Section: Lipid Apheresismentioning
confidence: 97%
“…Plasmapheresis has been suggested as a treatment for resistant complications of PBC going as far back as the 1970s. 80,81 However, its use in pruritus related to cholestasis is still in the experimental phase. A recent study of 17 patients with PBC with refractory pruritus and who received 129 sessions of plasmapheresis over 40 hospital admissions has been published.…”
Section: Management Of Itch In Pbcmentioning
confidence: 99%